Enhancing Early Reading Skills Through Problem-Based Learning: A Classroom Action Research with Students with Intellectual Disabilities - Ona, Maria Guida Prayitna; Purwanta, Edi (Papanda Publisher, 2025)
Early reading skills constitute fundamental competencies for academic success, yet students with intellectual disabilities face significant challenges in literacy acquisition. Problem-Based Learning (PBL) has emerged as a promising pedagogical approach, but limited research exists on its effectiveness for improving reading skills among students with cognitive limitations. This study investigated the implementation of PBL methodology to enhance early reading competencies in an inclusive elementary classroom setting. A Classroom Action Research design employing the Kemmis and McTaggart model was conducted over two cycles with 24 sixth-grade students at SDN 013 Bengalon, including one student with diagnosed intellectual disability. The intervention utilized PBL methodology integrated with picture story books and letter cards. Data collection employed oral reading assessments evaluating pronunciation accuracy, intonation, fluency, and voice clarity, alongside structured observations. Each cycle consisted of planning, action, observation, and reflection phases across four intervention meetings. Systematic implementation of PBL yielded substantial improvements in reading competencies. Class average scores increased from 68 to 92 points, while proficiency rates advanced from 62.5% to 100%. The student with intellectual disability demonstrated remarkable progress, improving from 40 to 70 points across intervention cycles. Observational data revealed enhanced student engagement, collaborative participation, and social interaction throughout the implementation period. PBL methodology effectively improves early reading skills among diverse learners, including students with intellectual disabilities. The collaborative, contextual approach successfully addresses both academic and social development needs within inclusive classroom environments. These findings suggest that PBL can serve as a universal design for learning approach, challenging traditional assumptions about segregated special education requirements and advocating for inclusive pedagogical practices.